2019
DOI: 10.1016/j.molmet.2019.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced hypothalamic dysfunction and metabolic disease, and the therapeutic potential of polyphenols

Abstract: Background The prevalence of obesity and metabolic diseases continues to rise globally. The increased consumption of unhealthy energy-rich diets that are high in fat and sugars results in oxidative stress and inflammation leading to hypothalamic dysfunction, which has been linked with these diseases. Conversely, diets rich in polyphenols, which are phytochemicals known for their antioxidant and anti-inflammatory properties, are associated with a reduced risk for developing metabolic diseases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 115 publications
0
26
0
Order By: Relevance
“…Therefore, in both the central and peripheral tissues, uncontrolled or chronic inflammation accompanies IR ( Saltiel and Olefsky, 2017 ). Interestingly, inflammation also underlies hypothalamic dysfunction in obesity ( Samodien et al, 2019 ). New evidence indicates that it is the inflammation and stress of the endoplasmic reticulum that are critical pathogenetic events in the central and peripheral IR in metabolic disorders ( Arruda et al, 2011 ).…”
Section: Metabolic Hallmarks Of Aging and Their Role In The Cognitivementioning
confidence: 99%
“…Therefore, in both the central and peripheral tissues, uncontrolled or chronic inflammation accompanies IR ( Saltiel and Olefsky, 2017 ). Interestingly, inflammation also underlies hypothalamic dysfunction in obesity ( Samodien et al, 2019 ). New evidence indicates that it is the inflammation and stress of the endoplasmic reticulum that are critical pathogenetic events in the central and peripheral IR in metabolic disorders ( Arruda et al, 2011 ).…”
Section: Metabolic Hallmarks Of Aging and Their Role In The Cognitivementioning
confidence: 99%
“…They are widely distributed in fruits, vegetables, and highly present in foods like legumes, cocoa, some cereals as well as in some beverages, such as tea, coffee and wine [ 29 ]. Polyphenols are not essential nutrients for humans but research in nutrition, including epidemiological studies, randomized controlled trials, in vivo and in vitro assays with animal models and cell lines, has shown that long-term and acute intakes can have beneficial effects on weight management and chronic diseases such as CVD, obesity, type 2 diabetes, the onset and development of some cancers and cognitive function [ 13 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Polyphenols and Metabolismmentioning
confidence: 99%
“…On the other side, diet-induced hypothalamic inflammation and mitochondrial dysfunction result in the onset and development of obesity and related metabolic diseases. It has been shown that, in rats, high fat diet (HFD) induces metabolic inflammation in the central nervous system (CNS), particularity in the hypothalamus [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Caloric restriction may also represent another efficient approach [ 106 ]. Several studies also support the role of diets rich in polyphenols, to modulate the inflammatory response and oxidative stress in the hypothalamus [ 107 ]. Moreover, exercise has a beneficial effect in the reduction of body weight alone but also in tempering the installed hypothalamic inflammation by decreasing microglia activation and by improving glucose intolerance [ 108 ].…”
Section: Discussionmentioning
confidence: 99%